The Relationship between Educational Pathways and Occupational Outcomes at the Intersection of Gender and Social Origin - Zimmermann, Barbara (Social Inclusion, 2019)
In this article, we are interested in the differences in the educational pathways and subsequent labour market outcomes by social origin and gender. We apply sequence analyses to model the educational trajectories and conduct regression analyses to determine how the individual’s own social status and the salary at labour market entry differs. First, our results show that educational pathways vary by parental status and gender when controlling for reading and mathematics/science skills. Men and pupils with a lower socioeconomic background are overrepresented in vocational education, whereas women and pupils with a more privileged socioeconomic background more often pursue general and academic tracks. Second, these different trajectories lead to unequal occupational status and income. Besides these indirect effects, significant direct effects of parental status and gender on the individual’s own occupational status and salary can be found. Together, these findings provide a broad overview of the emergence of inequalities by gender and social origin over the early life course, ranging from differences in skills learned in school to labour market outcomes.